2018
DOI: 10.17126/joralres.2018.034
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency-Associated Burkitt’s lymphoma in pediatric patients: a clinical case report

Abstract: Burkitt's lymphoma, a form of non-Hodgkin lymphoma, is a neoplastic monoclonal proliferation of lymphoid cells in areas of the immune system. It can occur in HIV-positive patients, as AIDS is related to the development of non-Hodgkin lymphoma. Burkitt's lymphoma is a rare subtype, highly prevalent in patients with AIDS. Incisional biopsy, in situ hybridization and computerized axial tomography are the appropriate tests to determine the characterize of the lesions. The case of a 4-year-old HIV-positive patient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…There are few case reports of children with immunodeficiencyassociated BL in the world. 54,55,56 The sample size of HIV-negative adults (n = 4) could not be reliably analysed and additional research is required. An international study of 52 immunocompetent adults with BL showed an event-free survival rate of 65% at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…There are few case reports of children with immunodeficiencyassociated BL in the world. 54,55,56 The sample size of HIV-negative adults (n = 4) could not be reliably analysed and additional research is required. An international study of 52 immunocompetent adults with BL showed an event-free survival rate of 65% at 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Timely and accurate diagnosis of the BL is challenging but crucial. The standard treatment of BL in paediatric age is chemotherapy, but sometimes surgery may be added [8]. In this study, we discuss the clinical profile, management, and outcome of nasopharyngeal BL in paediatric age at a tertiary care teaching hospital in eastern India.…”
Section: Introductionmentioning
confidence: 99%